Analisis Kemampuan Pemecahan Masalah untuk Topik Usaha dan Energi pada Siswa SMA di Palangka Raya - Dinata, Pri Ariadi Cahya; Hartanto, Theo Jhoni; Sari, Desy Kumala; Wati, Mustika; Dewantara, Dewi; Sapetrus, Frency; Siloam, Kristanoval (FKIP Universitas Palangka Raya, 2024)
Problem solving is a vital ability for students to be able to solve physics questions. Physics learning in the classroom needs to improve and develop this ability in students. Therefore, this research aims to analyze the students' problem-solving abilities as learning outcomes that have been obtained by high school students in Palangkaraya City. The research type is descriptive research with survey methods. The instrument used was a problem-solving ability test for the topic of work and energy. It was implemented on 155 12th grade in Palangkaraya. The results were analyzed quantitatively to identify the ability to describe problems, identify variables, plan solutions, implement plans, and check and evaluate the process. The results show that the students’ ability to describe problems and identify variables is better than other abilities. They can identify the variables in the questions and describe the physical situations. In addition, when the questions involve formula analysis and calculations, many students are unable to identify the equations that must be applied. They also have problems with their mathematical abilities to obtain the final answer. Educators need to concern these results in designing work and energy learning that can accommodate students' problem-solving abilities.